Geographical origins and economic consequences of language structures - Oded Galor; Ömar Özak; Assaf Sarid (Brown University, Department of Economics, 2016)
This research explores the economic causes and consequences of language structures. It advances the hypothesis and establishes empirically that variations in pre-industrial geographical characteristics that were conducive to higher return to agricultural investment, larger gender gap in agricultural productivity, and more hierarchical society, are at the root of existing cross-language variations in the presence of the future tense, grammatical gender, and politeness distinctions. Moreover, the research suggests that while language structures have largely reflected the coding of past human experience and in particular the range of ancestral cultural traits in society, they independently affected human behavior and economic outcomes.
Keywords: I25; J24; O1; Z10; 330; Cultural Evolution; Language Structure; Comparative Development; Future Tense; Politeness Distinctions; Grammatical Gender; Human Capital; Education